Evaluation the Authenticity of Wood Species in Sri Lankan Timber Market - Siriwardana, V.R.A.; Muthumala, C.K. (University of Sri Jayewardenepura 2018, 2018)
Attached
Keywords: Timber authenticity, Wood species, Local, Imported